Book Discussion: G.C. Bitros and A.D. Karayiannis, 2013, “Creative Crisis in Democracy and Economy” Springer –Verlag, Berlin Heidelberg - Kanas, Angelos (SPOUDAI Journal of Economics and Business, 2015)
G.C. Bitros and A.D. Karayiannis, 2013, “Creative Crisis in Democracy and Economy” Springer –Verlag, Berlin Heidelberg, ISBN 978-3-642-33421-4.